A Study On Technology Enhanced Travel Experiences In Empowering Women - Poopale Ratthinan, Senutha (2020)
Women's participation as an important entity of the travel industry both as producers and consumers is growing. On the other hand, technology is transforming the way travel is researched, purchased, provided and experienced. The rise of new technologies has not only enhanced the travel experiences but also created greater opportunities for women to travel. The enhanced experiences contribute toward empowerment by giving women autonomy in making decisions, notable purchasing power and choosing better outcomes of journey experiences